Organizational Management Imbalance from the Qur'anic Perspective - Supodo, Yuli; Sarnoto, Ahmad Zain (Tebuireng: Journal of Islamic Studies and Society, 2025)
Modern organizational management, rooted in secular Western paradigms, achieves operational efficiency through classical functions planning, organizing, leading, and controlling yet exhibits spiritual-ethical imbalances manifesting as corruption, bureaucratic pathologies, and commercialization in Islamic education institutions. This library research employs Qur'anic content analysis on 12 thematic verses (QS. Yusuf:47-49; Ali Imran:159; Al-Mujadilah:7) to integrate classical management (Terry, Fayol) with Islamic principles (tauhid, syura, muraqabah), producing a holistic Islamic Management Cycle based on Falah for sustainable success (worldly productivity + spiritual blessing). Findings reveal: (1) tauhid (QS. Adz-Dzariyat:56) transforms organizations into worship ecosystems; (2) systematic integration yields Yusufi planning, maslahah organizing, syura leading, muraqabah controlling; (3) 4-stage Maturity Model (Diagnosis 2025→Falah 2035) with KPIs (accreditation A, taqwa 90%, employability 95%). Visualizations (Tables 1-5, Figures 1-2) provide PTIQ Jakarta's 2025-2035 blueprint, addressing 68% PTKIN governance stagnation. Recommendations target academics (empirical validation), practitioners (Renstra implementation), and policymakers (national curriculum integration), bridging Western theory-Islamic praxis gaps for falah-oriented transformation.